2018
DOI: 10.3390/e20080582
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Heat Transfer in Two-Dimensional Turbulent Rayleigh-Bénard Convection at Various Prandtl Number

Abstract: Statistics of heat transfer in two-dimensional (2D) turbulent Rayleigh-Bénard (RB) convection for Pr = 6, 20, 100 and 10 6 are investigated using the lattice Boltzmann method (LBM). Our results reveal that the large scale circulation is gradually broken up into small scale structures plumes with the increase of Pr, the large scale circulation disappears with increasing Pr, and a great deal of smaller thermal plumes vertically rise and fall from the bottom to top walls. It is further indicated that vertical mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The flow structure for the highest value of the magnetic field presents a model picture of turbulence-with high velocity vectors, thermal plumes meandering on the active surfaces and dissipating as a result of the intensity of the flow. This obtained flow field is almost identical to the results presented in [46] for Prandtl number 100 and Ra = 5.4 × 10 9 (Prandtl number in ∆T = 11 • C is equal to 98.7 and Ra TM = 1.12 × 10 9 ). Therefore, it can be concluded that the strong magnetic field applied to the paramagnetic fluid can accelerate the full turbulence formation in comparison to free convection without changing the thermal conditions of the system.…”
Section: Velocitiessupporting
confidence: 87%
“…The flow structure for the highest value of the magnetic field presents a model picture of turbulence-with high velocity vectors, thermal plumes meandering on the active surfaces and dissipating as a result of the intensity of the flow. This obtained flow field is almost identical to the results presented in [46] for Prandtl number 100 and Ra = 5.4 × 10 9 (Prandtl number in ∆T = 11 • C is equal to 98.7 and Ra TM = 1.12 × 10 9 ). Therefore, it can be concluded that the strong magnetic field applied to the paramagnetic fluid can accelerate the full turbulence formation in comparison to free convection without changing the thermal conditions of the system.…”
Section: Velocitiessupporting
confidence: 87%
“…The Rayleigh–Taylor instability is a well-known and widely studied gravity-driven effect occurring when a layer of a heavier fluid lies on top of another layer of a lighter fluid [ 38 , 39 , 40 ]. Perturbation at the interface between the two fluids causes the heavier one to penetrate the lighter fluid.…”
Section: Numerical Applicationsmentioning
confidence: 99%
“…Some related work can be seen in references [ 34 , 35 , 36 , 37 , 38 ]. Yikun Wei et al [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] investigated thermal behavior, heat transfer, and entropy using the Lattice Boltzmann Method and also a numerical approach.…”
Section: Introductionmentioning
confidence: 99%